The Action Of Coleus Aromaticus As A Potential Wound Healing Agent In Experimentally Induced Diabetic Mice - Kalesware Muniandy; Zaiton Hassan2; Mohd Hafez Mohd Isa (Persatuan Saintis Muslim Malaysia, 2024)
PERINTIS E-Journal, 2014, Vol. 4, No. 1, pp.1-30